ARMENIAN-IRANIAN CULTURAL RELATIONS IN 1991-2005 - Mkrtcan, Karen Gurgenovic; Abelan, Arpine Arturovna; Melkonan, Kristine Feliksovna (History, Archeology and Ethnography of the Caucasus, 2025)
The article is devoted to the analysis of Armenian-Iranian cultural ties as manifestations of the peaceful coexistence of Christianity and Islam in the region. Accordingly, from a chronological point of view, the study presents Armenian-Iranian cultural ties from the moment Armenia gained independence in 1991 and until the mid-2000s. It is known that even in the Soviet years, there were cultural ties between Soviet Armenia and the Islamic Republic of Iran under the supervision of Moscow. However, the establishment of diplomatic relations between Armenia and Iran on February 9, 1992 in Tehran allowed the parties to start the process of developing comprehensive relations already at the level of two subjects of international law, as well as to develop cultural ties of another level. Over the past years, cooperation in the field of culture has expanded due to the signing of new interstate agreements in various branches of this field. It is obvious that the crossing of the paths of Islam and Christianity gave this cooperation a special civilizational form. In other words, Armenian-Iranian cultural ties strive to become a symbol of the stability of ancient civilization and a model to follow not only in the South Caucasus, but also in the Middle East - in a region with complex and conflicting interests. Armenian-Iranian cultural cooperation in this historical-geographic environment, known for tense conflicts and various forms of their manifestation, is, figuratively speaking, an oasis of peace. The topic of this study has not only theoretical and historical, but also practical and cultural significance, which makes it more relevant in the context of intercultural-intercivilizational-interreligious dialogue, which is necessary in the regions of the Middle East and the Caucasus, which are characterized by military and political tension.